PSYCHOLOGY OF MEDICAL MANAGERS - Khayitova , Iroda Ilhomovna; Murodullayev , Mironshokh; Usmonova , Nigina (Innovative Development in Educational Activities, 2023)
The role of medical managers within healthcare institutions is vital, often serving as the bridge between healthcare providers and efficient, patient-centered care. This article delves into the multifaceted world of medical management, with a particular focus on the psychology behind the decisions, leadership, and challenges faced by these professionals.